2018
DOI: 10.20471/acc.2018.57.01.22
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Optic Neuropathy – Case Report with Discussion on Diagnostic Procedures and Therapy

Abstract: SUMMARY – Traumatic optic neuropathy (TON) is a serious vision threatening condition that can be caused by ocular or head trauma. Indirect damage to the optic nerve is the most common form of TON occurring in 0.5% to 5% of all closed head trauma cases. Although the degree of visual loss after indirect TON may vary, approximately 50% of all patients are left with ‘light perception’ or ‘no light perception’ vision, making TON a significant cause of permanent vision loss. We present a 47-year-old male patient wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“… It was found that no individuals with optic nerve injury recovered to their baseline visual acuity, and those with ocular motor manifestations had variable recovery. Case Reports Kal et al 19 Male 22 Abducens nerve palsy and Horner Syndrome Cannot be Determined Sinawat et al 29 Male 47 Cortical blindness Bilateral loss of visual acuity Ahmad Fauzi et al 36 Male 20 Bitemporal hemianopia secondary to traumatic chiasmal syndrome Unilateral loss of visual acuity Sherman et al 42 Male 31 Traumatic optic neuropathy Bilateral loss of visual acuity Gotfried et al 60 Female 45 Ptosis caused by complete third nerve palsy Cannot be Determined Vien et al 65 Male 25 Transsynaptic retrograde degeneration and homonymous hemianopsia Full recovery of VA Alderazi et al 72 Male 45 Right carotid-cavernous fistula Cannot be Determined Meena et al 76 Male 41 Optic nerve transection Unilateral blindness Kastelan et al 79 Male 47 Traumatic optic neuropathy Full recovery of VA …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… It was found that no individuals with optic nerve injury recovered to their baseline visual acuity, and those with ocular motor manifestations had variable recovery. Case Reports Kal et al 19 Male 22 Abducens nerve palsy and Horner Syndrome Cannot be Determined Sinawat et al 29 Male 47 Cortical blindness Bilateral loss of visual acuity Ahmad Fauzi et al 36 Male 20 Bitemporal hemianopia secondary to traumatic chiasmal syndrome Unilateral loss of visual acuity Sherman et al 42 Male 31 Traumatic optic neuropathy Bilateral loss of visual acuity Gotfried et al 60 Female 45 Ptosis caused by complete third nerve palsy Cannot be Determined Vien et al 65 Male 25 Transsynaptic retrograde degeneration and homonymous hemianopsia Full recovery of VA Alderazi et al 72 Male 45 Right carotid-cavernous fistula Cannot be Determined Meena et al 76 Male 41 Optic nerve transection Unilateral blindness Kastelan et al 79 Male 47 Traumatic optic neuropathy Full recovery of VA …”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies were identified that described neuro-ophthalmic manifestations secondary to motorcycle accidents. 19 , 29 , 36 , 42 , 47 , 60 , 65 , 72 , 76 , 79–81 Only one of these 12 studies was not a case report and described the neuro-ophthalmic complications associated with motorcycle and moped accidents observed in two centers over an 18-year period. 47 This study described 94 motorcycle-associated neuro-ophthalmic injuries and 2 moped-associated neuro-ophthalmic injuries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rarity of TON and the compartment syndrome that may follow requires prompt treatment following injury. The decision to administer conservative therapy, intravenous steroids, decompressive surgery, or a combination of steroids and surgery remains based on a case-by-case approach [14]. Wu and colleagues [11] have advised treatment with methylprednisolone if a patient presents within 8 h of insult and optic canal decompression within 12-24 h of beginning medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TON'nin mümkün olduğunca erken, özellikle ilk 8 saatte tanımlanmasının ve antiödem tedavinin başlanmasının tedavinin başarısı açısından önemli olduğu gösterilmiştir. 11 Bizim olgumuzda tanının daha geç konması ve pulse steroid tedavisine travma sonrası 10. günde başlanmasına rağmen hastanın görme işlevlerinde düzelme olmuştur. İyi bir solunum ve dolaşım desteğinin olması ve hematom etrafındaki beyin ödemi için başlanan deksametazon tedavilerinin katkısı olduğunu düşünüyoruz.…”
Section: Discussionunclassified